2017
DOI: 10.1520/acem20160037
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Fine-Grained Soils Against Desiccation Cracking Using Sustainable Materials

Abstract: Desiccation cracking is a phenomenon commonly associated with the fine-grained soils, which initiates at their surface and subsequently propagates deeper inside their matrix. Hence, for safe and durable infrastructure development, stabilization of such soils becomes important. In order to stabilize these soils, cement, chemicals, and fibers have been employed by earlier researchers. However, in recent times, the ill effects of these stabilizers on the ecosystem have been realized, and hence their replacement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Researchers have also shown that some of the soil properties (soil index properties (workability) and compaction characteristics) of fine grained soils can be enhanced by the addition of pozzolanic fly ash (Nicholson and Kashyap 1993;Coka 2001;Pandian and Krishma 2003;Trzebiatowski et al, 2004;Terzi 2009). Furthermore, quite a number of studies on the use of compacted fine grain soil as liners and cover in waste containment application are reported (Liman, 2009;Nwaiwu, 2005, 2005a,b;Osinubi and Eberemu, 2006;Osinubi and Eberemu, 2009b;Osinubi and Amadi, 2006;Amadi, 2009, 2010;Jayanthi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also shown that some of the soil properties (soil index properties (workability) and compaction characteristics) of fine grained soils can be enhanced by the addition of pozzolanic fly ash (Nicholson and Kashyap 1993;Coka 2001;Pandian and Krishma 2003;Trzebiatowski et al, 2004;Terzi 2009). Furthermore, quite a number of studies on the use of compacted fine grain soil as liners and cover in waste containment application are reported (Liman, 2009;Nwaiwu, 2005, 2005a,b;Osinubi and Eberemu, 2006;Osinubi and Eberemu, 2009b;Osinubi and Amadi, 2006;Amadi, 2009, 2010;Jayanthi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in view the sustainable growth, ideally, strategies to utilize such waste, as a man-made resource, should have been practiced. In this context, it is heartening to note that these issues are being recognized by the researchers, planners, industries and the administration as a major threat for the society [40,63,64,90,91,168,169], and ready-to-adopt techniques that have potential to overcome this situation are being developed, marketed and implemented.…”
Section: Introductionmentioning
confidence: 99%
“…The CIF approach has been used in many studies (Mi, 1995;Miller et al, 1998;Yesiller et al, 2000;Li et al, 2016;Chaduvula et al 2017;Wang et al 2017;Jayanthi et al 2017) as a descriptor of the extent of surficial cracking.…”
Section: Introductionmentioning
confidence: 99%